Association between concern about falling and depression symptoms in cognitively impaired older adults: a cross-sectional study - Bruno Remígio Cavalcante; Mariana Ferreira de Souza; Muana Hiandra Pereira dos Passos; Hitalo Andrade da Silva; Andreya Karolyne Santos Vieira; Paulo Ricardo Pereira dos Santos; Rodrigo Cappato de Araújo (O Mundo da Saúde, 2021)
Concerns about falling and depressive symptomatology are well-known fall-risk factors in older people. However, whether both factors are inter-related it is not fully elucidated among individuals with cognitive issues. To shed light in this field, we analyzed the association between the concerns about falling and depressive symptoms in older adults with cognitive impairments. This cross-sectional study was composed of 67 community-dwelling cognitively impaired older adults(age: 71±5 years; sex: 78% female). We assessed their concerns about falling (independent) and depression symptoms (outcome) using the Falls Efficacy Scale - International (FESI) and the short-version of Geriatric Depression Scale (GDS-15), respectively. Covariates included age, sex, education, fall history, physical (Short-Physical Performance Battery), and cognitive function (Brazilian version of Montreal Cognitive Assessment). Linear regression models were performed in order to examine the independent relationship between FESI and GDS scores. All analyses were computed using STATA and significance was set at P<0.05. Participants with higher depressive symptoms (GDS ≥ 5 points) showed a significantly poor score on FESI (Mean difference: -5.3 points; 95%CI = -9.9 to -0.7; p=0.02). The regression model showed an association between the FESI and GDS-15 after adjustment for confounders (β=0.08; 95% CI= 0.02; 0.14), suggesting that higher concerns about falling are associated with higher depressive symptoms. Concerns about falling are associated with depressive symptoms among cognitively impaired older adults independently of overall physical function, global cognition, and fall history.